Isolation and mode of action of bacteriocin BacC1 produced by nonpathogenic Enterococcus faecium C1 - Goh, H F; Philip, K (Journal of dairy science, 2015)
Lactic acid bacteria are present in fermented food products and help to improve shelf life and enhance the flavor of the food. They also produce metabolites such as bacteriocins to prevent the growth of undesirable or pathogenic bacteria. In this study, Enterococcus faecium C1 isolated from fermented cow milk was able to produce bacteriocin BacC1 and inhibit the growth of selected food-spoilage bacteria. The bacteriocin was purified through 4 steps: ammonium sulfate precipitation, hydrophobic interaction column, a series of centrifugal steps, and finally reversed-phase HPLC. A membrane permeability test using SYTOX green dye (Invitrogen, Grand Island, NY) showed that the bacteriocin caused significant disruptions to the test bacterial membrane, as shown by transmission electron microscopy. The molecular weight of the BacC1 obtained from SDS-PAGE was around 10kDa, and N-terminal sequencing revealed a partial amino acid sequence of BacC1: GPXGPXGP. The bacterial strain was nonhemolytic and not antibiotic resistant. Therefore, it has high potential for application in the food industry as an antimicrobial agent to extend the shelf life of food products.